RATIONAL APPROACH IN THE TREATMENT OF WOMEN OF REPRODUCTIVE AGE WITH MASTALGIA AND MASTODYNIA - Markin, L.B.; Fartushok, T.V.; Fartushok, N.V.; Pylypchuk, I.S.; Flud, V.V.; Dzhalilova, E.A. (World of Medicine and Biology, 2024)
More than 82 % of women of reproductive age note pain in the mammary gland. Every fifth woman feels severe pain (mastalgia) and swelling (mastodynia) in the mammary gland. Cyclic mastalgia is combined with hyperprolactinemia. Hyperprolactinemia occurs when dopamine does not suppress pituitary function enough to reduce prolactin release. Agni casti fructus, known for its dopaminergic activity, relieves pain and discomfort in the mammary glands. 50 patients were under observation. Only 10 % of patients felt mild pain, 32 % experienced moderate pain, 50 % assessed it as severe, and 8 % experienced extreme pain. After the treatment, the complete absence of pain was noted by 76 % of patients. The results of the conducted studies indicate a high efficiency of 76 % and the safety of using Agni casti fructus in treating mastalgia and mastodynia. The high efficiency in the treatment of mastalgia and mastodynia with the herbal medicine Agni casti fructus without the additional use of hormonal drugs can be explained by the fact that this drug normalizes the hormonal balance of a woman.
Keywords: pain; mastalgia; mastodynia; Agni casti fructus; treatment